Aktivitas Antibakteri Kayu Siwak (Salvadora persica) Fraksi Eter terhadap Bakteri Staphylococcus aureus Secara In Vitro - Riza Amalia; Nurul Marfu'ah; Surya Amal (Pharmasipha : Pharmaceutical Journal of Islamic Pharmacy, 2018)
Using miswak is one of sunnah performed by Prophet Muhammad SAW and it contains a variety of compounds including these terpenoids, alkaloids, tannins and flavonoids which function as an antibacterial on the periodontal disease. Therefore, extraction and fractionation process were done to get the active compounds in miswak wood that has antibacterial activity against Staphylococcus aureus. This study is an experimental research with Complete Random Design methods. Ethanol extract separated using miswak from solvent of ether. Screening phytochemicals on thin Layer Chromatography (TLC) and test tube, the antibacterial activity was done using diffusion method with a concentration of 50% v/v, 25% v/v, 12.5% v/v and 6.25% v/v, metronidazole as a positive control and a DMSO as the negative control. The data obtained were then analyzed using One Way ANOVA test. Wood of miswak from ether fraction provide inhibition of 14.6-20.8 mm included strong category. The use of metronidazole as positive controls provide significant inhibitory against Staphylococcus aureus and the solvent DMSO as a negative control did not provide any inhibitory area. As for the description of the zone of inhibition against Staphylococcus aureus bacteria. Miswak wood from ether has antibacterial activity against Staphylococcus aureus with fraction of ether concentration of 12.5% v/v and smallest zone amounting 14.6 mm. Whereas at the greatest concentration found in the inhibition of 50% v/v with the average diameter of the zone of drag of 20.8 mm, with secondary metabolites contained in miswak fraction of ether is these terpenoids, alkaloids and tannins